Endogenous electric currents might guide rostral migration of neuroblasts. (18th January 2013) - Cao, Lin; Wei, Dongguang; Reid, Brian; Zhao, Siwei; Pu, Jin; Pan, Tingrui; Yamoah, Ebenezer N; Zhao, Min
Abstract : Mechanisms that guide directional migration of neuroblasts from the subventricular zone (SVZ) are not well understood. We report here that endogenous electric currents serve as a guidance cue for neuroblast migration. We identify the existence of naturally occurring electric currents (1.5±0.6 μA/cm 2, average field strength of ∼3 mV/mm) along the rostral migration path in adult mouse brain. Electric fields of similar strength direct migration of neuroblasts from the SVZ in culture and in brain slices. The purinergic receptor P2Y1 mediates this migration. The results indicate that naturally occurring electric currents serve as a new guidance mechanism for rostral neuronal migration. Endogenous electric currents might guide rostral migration of neuroblasts: This study reports naturally occurring electric currents and electric fields along the rostral migration path in adult mouse brain. The data indicate that electric fields might serve as guidance cues for neuroblast migration.